Žejni gozdovi črne jelše (Alnus glutinosa) - Cimperšek, Mitja (Gozdarski vestnik, 2013)
Alders are among the rare and overlooked tree species and the most important of the ones growing in Slovenia is black alder (Alnus glutinosa) forming peculiar mire and riparian forests. In this article we comparatively present two monodominant black alder associations: Carici elongatae-Alnetum in fens and Stellario nemorum-Alnetum in groves; due to the poor knowledge of ecology,hydrology, ethnobotanics, symbolics, and infrequence we often unduly despise and recklessly destroy.
Keywords: mokrišča; črna jelša; Alnus glutinosa; grez; log; varovalnost; etnobotanika